Cell‐Selective Encapsulation within Metal–Organic Framework Shells via Precursor‐Functionalized Aptamer Identification for Whole‐Cell Cancer Vaccine. Issue 3 (2nd February 2022) - Yang, Huihui; Zhang, Yanfei; Zeng, Leli; Yin, Wen; Xu, Yuzhi; Chen, Jun; Liu, Si‐Yang; Zou, Xiaoyong; He, Zhiyu; Dai, Zong
Abstract: Single‐cell encapsulation is an emerging technology to endow cells with various functions, of which developing new applications in vivo is in high demand. Currently, metal–organic frameworks (MOFs) that are used as nanometric shells to coat living cells, however, have not realized cell‐selective encapsulation. Here, a biocompatible and selective cell encapsulation strategy based on precursor‐functionalized nucleolin aptamer and in situ MOF mineralization on the aptamer‐identified cancer cell surface are developed. After MOF coating, the encapsulated cancer cells undergo immunogenic cell death, which is found associated with the changed cell stiffness (indicated by Young's modulus). The immunogenic dead cancer cells are used as whole‐cell cancer vaccines (WCCVs), forming the integral WCCV‐in‐shell structure with enhanced immunogenicity ascribing from the surface‐exposed calreticulin to promote dendritic cell recruitment, antigen presentation, and T‐cell activation. The major activation pathways in the immune response are identified including tumor necrosis factor signaling pathway, cytokine–cytokine receptor interaction, and Toll‐like receptor signaling pathway, suggesting the potential adjuvant effect of the MOF shells. After vaccination, WCCV‐in‐shell shows much better tumor immunoprophylaxis than either the imperfectly coated cancer cells or the traditional WCCV. This strategy is promising for the universal and facile development of novel whole‐cell vaccines. Abstract : By harnessing the cell identification via precursor‐functionalized aptamer, ZIF‐8 is specifically in situ grown on living cancer cells at biocompatible condition, forming the integral whole‐cell cancer vaccine (WCCV)‐in‐shell structure. With calreticulin surface exposure and entire tumor associated antigens, WCCV‐in‐shell has enhanced immunogenicity and shows the best preventive effect on tumorigenesis along with little safety concern.